2013
DOI: 10.1136/bcr-2013-009885
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyponatremia and MRI point to diagnosis of tuberculous meningitis in the Southwest USA

Abstract: A 21-year-old woman presented to the hospital with 3 days of headache, fever, mood disturbance and nausea. She had recently emigrated from India, and was noted to have a positive screening purified protein derivative tuberculosis skin test with normal chest x-ray. Meningeal signs were noted prompting lumbar puncture and initiation of presumptive treatment for bacterial meningitis. While tuberculous meningitis (TM) was entertained at admission, diagnosis was clouded by the rapid onset of symptoms and recent maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For a scoring system comparing TBM with VM, the Hristea scoring system 13 included CSF and clinical findings, duration of illness, and neurological status. Following this study, many subsequent published studies emphasized the importance of hyponatremia, which occurs in 30%–50% of patients in the first month of treatment, 15 33 as well as cranial nerve palsy, with the abducens (6th) nerve the most frequently affected. 16 In the present study, we have tried to create a new scoring system for differential diagnosis between TBM and VM.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For a scoring system comparing TBM with VM, the Hristea scoring system 13 included CSF and clinical findings, duration of illness, and neurological status. Following this study, many subsequent published studies emphasized the importance of hyponatremia, which occurs in 30%–50% of patients in the first month of treatment, 15 33 as well as cranial nerve palsy, with the abducens (6th) nerve the most frequently affected. 16 In the present study, we have tried to create a new scoring system for differential diagnosis between TBM and VM.…”
Section: Discussionmentioning
confidence: 82%
“…For decades, there have been many descriptions of assays testing meaningful factors in TBM, such as adenosine deaminase (ADA), lactic acid and LDH in CSF, procalcitonin, serum sodium, and cranial nerve palsy symptoms, among others. 15 16 31 32 33 34 However, each factor alone cannot distinguish between TBM and other forms of meningitis. Therefore, before TB culture results can be obtained, a simple diagnostic system that synthesizes statistically meaningful predictors is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Another study carried out by Goos M et al reported 53% prevalence of hyponatremia in patients with tuberculous meningitis which is almost similar with our findings 9 . According to previous research, the correlation between hyponatremia and tuberculous bacterial meningitis was 44.7%, with cerebral salt wasting syndrome affecting 50% of patients and the SIADH affecting 9% 10 . A previous study done by Jong et al reported low prevalence (37%) of hyponatremia in patients with tuberculous meningitis which is not in accordance with our study 11 .ss…”
Section: Discussionmentioning
confidence: 90%
“…One of the cases is of anterior callosal and frontal tuberculoma presenting with chronic psychosis and recent onset catatonia [5]. Another case where in mood disturbances in the form of depressive symptoms, cognitive difficulties and hyponatremia were presenting features of tubercular meningitis [6]. A case series about unusual presentations of tubercular meningitis had one of the cases presenting as paranoid psychosis [7].…”
Section: Discussionmentioning
confidence: 99%